A prolonged cholera outbreak caused by drinking contaminated stream water, Kyangwali refugee settlement, Hoima District, Western Uganda: 2018 - Fred Monje; Alex Riolexus Ario; Angella Musewa; Kenneth Bainomugisha; Bernadette Basuta Mirembe; Dativa Maria Aliddeki; Daniel Eurien; Godfrey Nsereko; Carol Nanziri; Esther Kisaakye; Vivian Ntono; Benon Kwesiga; et al. (BMC, 2020)
Abstract Background On 23 February 2018, the Uganda Ministry of Health (MOH) declared a cholera outbreak affecting more than 60 persons in Kyangwali Refugee Settlement, Hoima District, bordering the Democratic Republic of Congo (DRC). We investigated to determine the outbreak scope and risk factors for transmission, and recommend evidence-based control measures. Methods We defined a suspected case as sudden onset of watery diarrhoea in any person aged ≥ 2 years in Hoima District, 1 February-9 May 2018. A confirmed case was a suspected case with Vibrio cholerae cultured from a stool sample. We found cases by active community search and record reviews at Cholera Treatment Centres. We calculated case-fatality rates (CFR) and attack rates (AR) by sub-county and nationality. In a case-control study, we compared exposure factors among case- and control-households. We estimated the association between the exposures and outcome using Mantel-Haenszel method. We conducted an environmental assessment in the refugee settlement, including testing samples of stream water, tank water, and spring water for presence of fecal coliforms. We tested suspected cholera cases using cholera rapid diagnostic test (RDT) kits followed by culture for confirmation. Results We identified 2122 case-patients and 44 deaths (CFR = 2.1%). Case-patients originating from Demographic Republic of Congo were the most affected (AR = 15/1000). The overall attack rate in Hoima District was 3.2/1000, with Kyangwali sub-county being the most affected (AR = 13/1000). The outbreak lasted 4 months, which was a multiple point-source. Environmental assessment showed that a stream separating two villages in Kyangwali Refugee Settlement was a site of open defecation for refugees. Among three water sources tested, only stream water was feacally-contaminated, yielding > 100 CFU/100 ml. Of 130 stool samples tested, 124 (95%) yielded V. cholerae by culture. Stream water was most strongly associated with illness (odds ratio [OR] = 14.2, 95% CI: 1.5-133), although tank water also appeared to be independently associated with illness (OR = 11.6, 95% CI: 1.4-94). Persons who drank tank and stream water had a 17-fold higher odds of illness compared with persons who drank from other sources (OR = 17.3, 95% CI: 2.2-137). Conclusions Our investigation demonstrated that this was a prolonged cholera outbreak that affected four sub-counties and two divisions in Hoima District, and was associated with drinking of contaminated stream water. In addition, tank water also appears to be unsafe. We recommended boiling drinking water, increasing latrine coverage, and provision of safe water by the District and entire High Commission for refugees.